The Use of Spelling Bee to Improve Students’ English Vocabulary Mastery at SMP Negeri 11 Makassar - Sulviana Sulviana; Ichsan Mahendra (Edumaspul: Jurnal Pendidikan, 2021)
This research discussed about “The Use of Spelling Bee to Improve Students’ English Vocabulary Mastery at SMPN 11 Makassar”. The objectives of this research are to find out the improvement and interest of the students’ English vocabulary after using spelling bee. The researcher used quasi-experimental design with non-equivalent control group design. The population of this research of the seventh year students at SMPN 11 Makassar. It consisted of 40 students which divided into two group of class where 20 students from VII A as experiment class and 20 students from VII B as a control class. The independent variable of this research is spelling bee and the dependent variable of this research was students’ vocabulary mastery. The instrument of this research was vocabulary test used pre-test and post-test. This research used purposive sampling technique. The results of the research showed that score test spelling bee on pre-test in experiment class is 64.80 and score test pre-test in control class is 53.55. The score post-test in experiment class is 78.85 and score post-test in control class is 50.75. Based on the result of the questionnaire, the researcher concluded that H1 was accepted and H0 is rejected it means that using spelling bee was affective to improve the students English vocabulary of the seventh grade students at SMPN 11 Makassar. Therefore, the rating mean score questionnaire is 62.75, put in the category fairly